Electric Current Approach Studying Both Auroral Substorms and Solar Flares Together - Akasofu, Syun-Ichi (Frontiers in Astronomy and Space Sciences, 2020)
Auroral substorms and solar flares are basically various manifestations of electromagnetic energy dissipation, so that it is useful to consider both phenomena in terms of a chain of processes, consisting of power supply (dynamo), transmission (currents/circuits) and dissipation (auroral substorms, solar flares), the electric current approach. In this short review, we briefly describe both phenomena together on the basis of the chain process. It is shown that the introduction of a dynamo process in this consideration provides a step-by-step way of studying both phenomena. It is shown: (a) Both the solar wind-magnetosphere dynamo and a photospheric dynamo proposed by Lee et al. (1995) have enough power to accumulate enough energy for the explosive features of both phenomena, respectively. (b) For substorms, the power is accumulated in the inner magnetosphere and inflates it, and for flares the power is likely to be accumulated in a loop current along and above two-ribbon flares. (c) For substorms, the energy release (unloading) process deflates the inner magnetosphere, resulting in an earthward electric field, and for flares the disruption of the loop current suggested by Alfven (1950) may be responsible for the energy release. (d) The processes in (c) are responsible for the explosive features of both phenomena.